Professional competence assessment of dispensary pharmacy technician. A methodological strategy. - María Cristina Núñez Martínez (Medisur)
Background: The assessment of professional competences in one of the four principles the support training and improvement of human resources in health system; there are problems in this process that obstruct its correct assessment. Objective: To ratify a methodological strategy to solve gaps in the assessment process of technicians’ professional competences. Methods: Qualitative and Quantitative study. The ratification of this strategy was carried out through an intentional stratified sampling of graduated, experts and evaluators. This was applied with participative and integrative approach in Cienfuegos province between 2001 and 2004. Findings: It was proved that the strategy contributes to increase the quality of professional competences assessment process, and determines technicians´ learning needs on scientific bases and supports methodological and didactic training of professors, pedagogical assistants and directors. The individual satisfaction level express by strategy users is high and consulted experts approve it by major consensus. Conclusions: Proposed methodology has characteristics that allow it being applied and generalized to every working field within Dispensary Pharmacy and other technical specialities.